2021
DOI: 10.1128/jvi.00818-21
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection of Pregnant Ifnar1 −/− Mice Triggers Strain-Specific Differences in Fetal Outcomes

Abstract: Zika virus (ZIKV) is a flavivirus that causes a constellation of adverse fetal outcomes collectively termed Congenital Zika Syndrome (CZS). However, not all pregnancies exposed to ZIKV result in an infant with apparent defects. During the 2015-2016 American outbreak of ZIKV, CZS rates varied by geographic location. The underlying mechanisms responsible for this heterogeneity in outcomes have not been well defined. Therefore, we sought to characterize and compare the pathogenic potential of multiple Asian/Ameri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…There was surprisingly little inflammation in any placental structure. Zika virus (ZIKV) infection of pregnant IFNAR1 knockout mice via footpad injection can result in vertical transmission involving severe necrosis of the decidua and basal zone [ 33 , 34 ]; however, decidual necrosis in ZIKV-infected rodents and pregnant women [ 35 ] is not associated with adverse fetal outcomes such as death or microcephaly. Vertical transmission of human immunodeficiency virus in placentas from 1 st and 2 nd trimester abortions is also correlated with necrosis of the decidua [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was surprisingly little inflammation in any placental structure. Zika virus (ZIKV) infection of pregnant IFNAR1 knockout mice via footpad injection can result in vertical transmission involving severe necrosis of the decidua and basal zone [ 33 , 34 ]; however, decidual necrosis in ZIKV-infected rodents and pregnant women [ 35 ] is not associated with adverse fetal outcomes such as death or microcephaly. Vertical transmission of human immunodeficiency virus in placentas from 1 st and 2 nd trimester abortions is also correlated with necrosis of the decidua [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Asian-lineage ZIKV, African-lineage ZIKV infection in pregnant mice is more likely to cause fetal demise than birth defects [ 16 , 17 ]. Aubry et al reported higher rates of fetal reabsorption in mouse pregnancies infected with African-lineage ZIKV, whereas infection with Asian-lineage resulted in varying capacities to cause fetal harm including fetal brain abnormalities as well as fetal death/resorption [ 16 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Asian-lineage ZIKV, African- lineage ZIKV infection in pregnant mice is more likely to cause fetal demise than birth defects [17] [18]. Aubry et al reported higher rates of fetal reabsorption in mouse pregnancies infected with African-lineage ZIKV, whereas infection with Asian-lineage resulted in varying capacities to cause fetal harm including fetal brain abnormalities as well as fetal death/resorption [17] [21].…”
Section: Introductionmentioning
confidence: 99%